Creating Short-term Classes on Unification in South KoreanUniversities - Lee, Andrea Rakushin; Hak, Soo Yoo; Bailey, Daniel R. (Faculty of Education, 2020)
Young adults will be the next generation of leaders, and it is critical for them to be cognizant of major issues that impact society. Unification is a significant issue in South Korea, especially in light of the recent summits between South and North Korea. This study is rooted in principles of peace education to promote peaceful discourse related to unification issues. Unification education plays an important role in K-12 education in South Korea; however, it is not prioritized at the university level. This case study, which included open-ended surveys, interviews, and focus groups, explored South Korean university students' (n=33) views of creating short -term classes on unification and the types of topics that they think should be taught in these classes. Primary results indicate that most participants expressed interest in taking short-term classes on unification issues. The paper also includes practical implications that can be considered when developing short-term classes on unification in South Korean universities.